1995
DOI: 10.1136/gut.36.5.696
|View full text |Cite
|
Sign up to set email alerts
|

South Asian and European colitics show characteristic differences in colonic mucus glycoprotein type and turnover.

Abstract: (Gut 1995; 36: 696-702)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 29 publications
(7 reference statements)
0
20
0
Order By: Relevance
“…In brief, slides were immersed in HID solution for 18-24 h (Mowry 1963;Spicer 1965;Probert et al 1995). After washing in 3% acetic acid, slides were then immersed in alcian blue (10 mg/ml) solution (pH 2.5) for 30 min.…”
Section: Histochemical Methodsmentioning
confidence: 99%
“…In brief, slides were immersed in HID solution for 18-24 h (Mowry 1963;Spicer 1965;Probert et al 1995). After washing in 3% acetic acid, slides were then immersed in alcian blue (10 mg/ml) solution (pH 2.5) for 30 min.…”
Section: Histochemical Methodsmentioning
confidence: 99%
“…8 -10 In addition, a study from Leicestershire, United Kingdom, showed that the pattern of colonic mucin synthesized in migrant South Asian patients with UC differs with that in European patients with UC. 11 Another study from Leicestershire also suggested that migrant South Asian patients with UC have a lower risk of colectomy than do European patients. 12 These results suggest that there could be some differences between Asian and Western populations in the development and clinical course of UC.…”
mentioning
confidence: 97%
“…IBD is most common in highly industrialized temperate regions and is rare in tropical countries with poor sanitation and overcrowding (17). The rarity of IBD in tropical countries cannot be explained on the basis of genetics alone, as descendants of immigrants from such countries acquire the higher risk of IBD of the adopted developed country (32,40). These observations underscore the importance of environmental factors in the expression of IBD and have led to the development of the "hygiene hypothesis" of IBD, that is, that IBD occurs more commonly in societies where the prevalence of chronic enteric infestation is low (17).…”
mentioning
confidence: 99%